Oral white patches in a national sample of medical HIV patients in the era of HAART - Marcus M, Maida CA, Freed JR, Younai F, Coulter ID, Der-Martirosian C, Liu H, (Blackwell Synergy, 2005)
Several types of HIV-related oral mucosal conditions have been reported to occur during the course of HIV disease progression.